2009
DOI: 10.1007/s00420-009-0484-8
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular response to an acute 1800-μT, 60-Hz magnetic field exposure in humans

Abstract: The MF used in this experiment did not affect cardiovascular parameters. Although an alternative explanation for why skin surface temperatures decreased in the sham and not in the real exposure condition is presented, the possibility of a MF effect cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
2
14
2
1
Order By: Relevance
“…The absence of HR effects lends support to the body of evidence, suggesting ELF MF do not affect the HR. These findings are consistent with the results observed in our previous work using an 1,800-lT MF exposure chamber (McNamee et al 2010) as well as others Sait et al 2006;Ghione et al 2005;Kurokawa et al 2003). It should be pointed out that in the current paper, the HR is recorded during a 1-h period of MF exposure at both 15 and 30 min after the field has been turned on.…”
Section: Skin Blood Perfusionsupporting
confidence: 94%
See 3 more Smart Citations
“…The absence of HR effects lends support to the body of evidence, suggesting ELF MF do not affect the HR. These findings are consistent with the results observed in our previous work using an 1,800-lT MF exposure chamber (McNamee et al 2010) as well as others Sait et al 2006;Ghione et al 2005;Kurokawa et al 2003). It should be pointed out that in the current paper, the HR is recorded during a 1-h period of MF exposure at both 15 and 30 min after the field has been turned on.…”
Section: Skin Blood Perfusionsupporting
confidence: 94%
“…Previous preliminary work in our laboratory has suggested an effect of a pulsed 60-Hz, 200-lT (peak) ELF MF exposure session on microcirculation in rats (Hensel et al 2003). Additionally, beyond the positive results from Hensel et al (2003), our 1,800-lT study indicated that skin surface temperature might have been modulated by MF exposure conditions (McNamee et al 2010). In the absence of an alternative explanation, it was not possible to rule out an MF exposure effect on skin surface temperature.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Mimo licznych badań dotyczących oddziaływania pola magnetycznego oraz biostymulacji laserowej na organizm, wiele efektów biologicznych, będących wynikiem ich działania, nadal pozostaje niewyjaśnionych [26]. Dlatego w praktyce terapię objawu Raynauda rozpoczyna się najczęściej od leczenia farmakologicznego, pozostawiając postępowanie fizjoterapeutyczne jako uzupełnienie bądź alternatywę, zwłaszcza w przypadku wystąpienia działań niepożądanych.…”
unclassified